Creating Resilient Futures Integrating Disaster Risk Reduction, Sustainable Development Goals and Climate Change Adaptation Agendas - Flood, Stephen; Jerez Columbié, Yairen; Le Tissier, Martin; O'Dwyer, Barry (Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This excellent text recognises that efforts towards improving development outcomes must work in concert with strategies which promote planetary health and support the transition to a sustainable and climate-resilient future. - Rt Hon Helen Clark, Patron, The Helen Clark Foundation, Auckland, New Zealand. The threat multiplier of climate change is carefully used to examine best practice in a series of excellent case studies exploring the three related responses of disaster risk reduction, sustainable development and climate change adaptation. -Emeritus Professor John Sweeney, Irish Climate Analysis and Research UnitS (ICARUS), Maynooth University, Ireland This book provides concrete examples, through case studies from Ireland and around the world, to help illustrate what it means to think and act simultaneously on development, disasters and climate. - Dr. Lisa Schipper, Environmental Social Science Research Fellow, Environmental Change Institute, University of Oxford, United Kingdom. This open access edited volume critically examines the coherence building opportunity between Climate Change Adaptation, the Sustainable Development Goals and Disaster Risk Reduction agendas. The authors consider opportunities to address the global challenge of developing resilience, as an integrated development continuum instead of through independent and siloed agendas. Stephen Flood is an environmental social science researcher working on various aspects of climate change adaptation, sustainability and resilience. He is based at the Irish Climate Analysis and Research Units (ICARUS), Maynooth University. Yairen Jerez Columbié investigates cultural exchange, postcolonial ecologies and the sociohistorical and cultural dimensions of environmental challenges. She is an Assistant Professor in Latin American Studies and Intercultural Communication atTrinity College Dublin. Martin Le Tissier is the lead PI for the Identifying Interactions for SDG Implementation in Ireland and Achieving Resilience in the Marine and Coastal Environment of Ireland EPA funded projects based at MaREI. Barry O'Dwyer is lead researcher in the area of impacts and adaptation at MaREI and is leading the development and delivery of Climate Ireland, Ireland's national resource of climate change and adaptation information.